2016
DOI: 10.4103/0973-1482.154925
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effect of carvacrol on 1,2-dimethylhydrazine induced experimental colon carcinogenesis

Abstract: The results of this study suggest that carvacrol at a dose of 40 mg/kg b.wt showed a significant beneficial effect against chemically-induced colon carcinogenesis in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In the current study, the major markers of oxidative stress response were found to be increased including LPO and NO, concurrently with the depletion of glutathione (GSH) and related redox cycle enzymes like SOD and CAT. Lipid peroxidation is one of the important markers of oxidative damage and high level of MDA, the end products of lipid peroxidation, has been found after DMH treatment [18-19]. Consistent with previous studies, our findings also showed noteworthy elevation in the level of LPO after DMH injection.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, the major markers of oxidative stress response were found to be increased including LPO and NO, concurrently with the depletion of glutathione (GSH) and related redox cycle enzymes like SOD and CAT. Lipid peroxidation is one of the important markers of oxidative damage and high level of MDA, the end products of lipid peroxidation, has been found after DMH treatment [18-19]. Consistent with previous studies, our findings also showed noteworthy elevation in the level of LPO after DMH injection.…”
Section: Discussionsupporting
confidence: 82%
“…Carvacrol supplementation significantly improved the weight gain and growth rate of animals with colon cancer induced by 1,2-dimethylhydrazine (DMH), exhibiting a lower incidence of tumors and pre-neoplastic lesions, along with a reduction in oxidative stress damage (higher levels of GSH, GPx, GR, SOD and CAT), suggesting that carvacrol presents chemopreventive effects ( Sivaranjani et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Carvacrol supplementation significantly improved the weight gain and growth rate of animals with colon cancer induced by 1,2dimethylhydrazine (DMH), exhibiting a lower incidence of tumors and pre-neoplastic lesions, along with a reduction in oxidative stress damage (higher levels of GSH, GPx, GR, SOD and CAT), suggesting that carvacrol presents chemopreventive effects (Sivaranjani et al, 2016). Li et al (2019) showed that tumor growth in mice with DENinduced hepatocarcinoma and treated with carvacrol was limited, revealing tumor cell reduction, rare mitotic figures, normal arrangement of cells, few microvessels, a central necrotic area on tumor tissue and a reduction of intrastromal and peritumor lymphocytes.…”
Section: Description Of In Vivo Studies With Carvacrol and Thymolmentioning
confidence: 99%
“…). Administration of carvacrol to adult male albino rats with chemical induced CRC, revealed that carvacrol reduced the number of colon tumors, dysplastic polyps, aberrant crypts foci, increased glutathione peroxidase and glutathione reductase activities and restored levels of liver peroxidation products [183]. Moreover, combined treatment between carvacrol and X-radiation significantly decreased tumor incidence [200].…”
Section: In Vivo Studies In Crc Animal Modelsmentioning
confidence: 99%